Cooperation triggers nitrogen removal and algal inhibition by actinomycetes during landscape water treatment: Performance and metabolic activity. (July 2022) - Ma, Ben; Zhang, Haihan; Huang, Tinglin; Chen, Shengnan; Sun, Weimin; Yang, Wanqiu; Liu, Hanyan; Liu, Xiang; Niu, Limin; Yang, Fan; Yu, Jimeng
Graphical abstract: Highlights: Nitrogen removal enhanced obviously by co-culture inefficiency actinomycetes. Co-culture promoted organic carbon utilization and cell growth. Co-culture promoted cellular metabolic and carbon source metabolic activity. Co-culture had a high inhibitory effect in removal of algal in landscape water. Co-culture destroyed the diversity of indigenous denitrifying bacterial community. Abstract: The actinomycetes strain Streptomyces sp. XD-11-9-3 and Streptomyces sp. 5 were isolated and presented poor denitrification performance. Co-culture of actinomycetes triggers nitrogen removal capacity under aerobic conditions (reduced 96% of total nitrogen). Nitrogen balance analysis presented that 71% of initial nitrogen converted as gaseous nitrogen. Moreover, co-culture increased the concentrations of adenosine triphosphate (>2.1 folds) and electron-transmission system activity (>1.5 folds) significantly. The co-culture presented excellent carbon source metabolism activity (especially amines and carboxylic acids) compared with monoculture. The removal efficiency of total nitrogen in the micro-polluted landscape water water reached 61% in the co-culture system, and the algal survival could be inhibited significantly. However, the dominant niche of the co-culture system restrained the diversity of the indigenous nirS -type denitrifying bacterial community. This study provided a novel pathway to the research of co-culture inefficiency aerobic denitrifier and further application in the restoration of polluted water.